Clinical outcomes of sedation during emergency endoscopic band ligation for variceal bleeding: Multicenter cohort study. Issue 6 (12th March 2020) - Park, Chan Hyuk; Park, Se Woo; Jung, Jang Han; Kim, Gyeong Guk; Choi, Se Young; Kim, Eun Sun; In, Dong Hyun; Kim, Hong Deok
Abstract : Background and Aims: Few studies have directly compared the efficacy of sedated‐ and un‐sedated endoscopic variceal ligation (EVL) for acute variceal bleeding. We aimed to determine whether sedation during EVL in patients with variceal bleeding is safe and effective. Methods: We analyzed data from patients who underwent EVL for acute variceal bleeding according to sedation in six hospitals of Hallym University Medical Center. The primary endpoint was treatment failure, defined as a failure to control bleeding, death during EVL, or rebleeding within 5 days. Secondary endpoints included the procedure time, adverse events, and 30‐day mortality. Results: Of 1, 300 patients who were included, only 430 (33.1%) received sedation during EVL. Propofol alone was used for sedation in 85% of sedated‐EVLs. The mean procedure time in the sedation group was shorter than that of the non‐sedation group (12.4 ± 9.5 min versus 13.8 ± 9.4 min, P  = 0.010). The proportion of treatment failure did not differ between the groups (7.4% versus 9.1%, P  = 0.374). In the multivariable analysis, an AIMS65 score ≥2 and blood transfusion within 72 hours were associated with treatment failure of EVL; however, the use of sedation was not (odds ratio [95% confidence interval (CI)] = 0.96 [0.60–1.51]). Adverse events during EVL and hepatic encephalopathy did not differ between the two groups. Sedation also did not affect the 30‐day mortality (hazard ratio [95% CI] = 0.99 [0.66–1.47]). Conclusion: Sedation reduced the procedure time of EVL. Sedation is safe to use during EVL for variceal bleeding in patients with cirrhosis.